2017
DOI: 10.21037/acs.2017.07.11
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation in nonagenarians: selectively feasible or extravagantly futile?

Abstract: A growing number of nonagenarians is recorded as life expectancy increases. Unfortunately, this extreme-aged group is plagued by increased prevalence of aortic stenosis amidst a higher occurrence of comorbidities that pose dilemmas to cardiologists and cardiac surgeons when having to choose a conservative or interventional treatment modality, and a surgical or transcatheter aortic valve implantation (TAVI) approach. TAVI is an expensive procedure, which also confers a higher mortality and morbidity risk in non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(58 reference statements)
1
3
0
Order By: Relevance
“…Manolis et al demonstrated that, in nonagenarians who underwent TAVR, bleeding and vascular complications ranged from 9% to 34% (average 16%), and stroke risk ranged from 2% to 18% (average 3–4%) [25]. Similarly, in this meta-analysis, we indicated that nonagenarians were associated with significantly increased rates of major or life-threatening bleeding, vascular complications and stroke of 20%, 35%, and 32%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Manolis et al demonstrated that, in nonagenarians who underwent TAVR, bleeding and vascular complications ranged from 9% to 34% (average 16%), and stroke risk ranged from 2% to 18% (average 3–4%) [25]. Similarly, in this meta-analysis, we indicated that nonagenarians were associated with significantly increased rates of major or life-threatening bleeding, vascular complications and stroke of 20%, 35%, and 32%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…There are several reports regarding the outcomes of TAVI in nonagenarians from Western countries. 8- 10 Yokoyama et al investigated the clinical outcomes after TAVI among Japanese nonagenarians. 11 They reported that early safety and 3-year mortality in nonagenarians were similar to those in patients aged <90 years.…”
Section: Discussionmentioning
confidence: 99%
“…Chronological age alone should not deprive patients of treatment -it is the physiological age that should determine a patient's candidacy for treatment of aortic valve stenosis. The aim of TAVI in this age group is primarily to make the patient feel better and to increase their quality of life but not necessarily to help them to live longer 3,4 .…”
Section: Heart Center Bonn University Hospital Bonn Bonn Germanymentioning
confidence: 99%
“…Selecting nonagenarian patients with a low comorbidity index and no extreme frailty, adopting a minimalistic approach, and paying attention to vascular access haemostasis may provide the elements that lead to a successful, desirable, and hopefully cost-effective outcome. Finally, quality-of-life studies are direly needed and eagerly awaited in this patient subpopulation in order to provide guidance on the patient selection process 3,4 .…”
Section: Article See Page 1489mentioning
confidence: 99%